Molecular basis of high temperature-induced bolting in lettuce revealed by multi-omics analysis - Jinghong Hao; Junwei Yang; Xiaofeng Liu; Gaoyang Pan; Yunfeng Li; Xiaolan Zhang; Yingyan Han; Shuangxi Fan; Zhaoyang Zhou (BMC Genomics, 2022)
Abstract Background High temperature induces early bolting in lettuce (Lactuca sativa L.), which affects both quality and production. However, the molecular mechanism underlying high temperature-induced bolting is still limited. Results We performed systematical analysis of morphology, transcriptome, miRNAs and methylome in lettuce under high temperature treatment. Through a comparison of RNA-Seq data between the control and the high temperature treated lettuces at different time points totally identified 2944 up-regulated genes and 2203 down-regulated genes, which cover three floral pathways including photoperiod, age and gibberellin (GA) pathways. Genome wide analysis of miRNAs and methylome during high temperature treatment indicated miRNAs and DNA methylation might play a role controlling gene expression during high temperature-induced bolting. miRNA targets included some protein kinase family proteins, which potentially play crucial roles in this process. Conclusions Together, our results propose a possible regulation network involved in high temperature-induced bolting.